Effects Of Exposure To Elevated Temperatures On The Bond Characteristics Between Normal Concrete Substrate And Ultra High Performance Fiber Reinforced Cementitious Composites - Zainal, Nur Liyana (2016)
UHPFRCC is usually applied to rehabilitation bridge of dam, building and other structures. Good bond strength between old concrete substrate and a newly overlaid repair material is a very important factor in assuring the performance of concrete repairs. However, the properties of concrete would be affected when it is exposed to high temperature. The quality assurance of the bond strength requires methods that can quantify the bond strength as well as identify the failure mode. A newly patented class of green UHPFRCC known as green Universiti Sains Malaysia reinforced concrete (GUSMRC) was developed. This concrete contains 50% of the cement total volume by pozzolanic material, ultra-fine POFA (UPOFA). The objective of this study is to evaluate the interfacial bonding characteristics between old concrete and new repair material after the composite is exposed to elevated temperatures of 100⁰C, 200⁰C, 300⁰C, 400⁰C and 500⁰C. GUSMRC was applied as the new repair material on the normal concrete substrate and the surface has been prepared / roughened either by sand blasting (SB) or grinding (GR). In addition, changes on the mechanical properties of the monolithic samples of the repair material as well as the normal concrete substrate were also evaluated after the exposure to the elevated temperatures. The characteristic of interfacial bond were assessed using the slant shear, pull-off, splitting tensile, and flexural strength test to evaluate the influence of two types of surface roughness and to evaluate the effect after the exposure to elevated temperatures. The results showed that the new green concrete overlay achieved good bond strength with the NC. Sand blasting surface treatment showed the excellent bonding properties compared to grinding before and after the exposure to the elevated temperatures. Mostly all the failure modes showed failures at NC substrate and automatically proved that the bondings between two layers are strong. The critical loss of strength for GUSMRC was recorded at 400⁰C and 500⁰C.